HOW IS THE INFLUENCE OF CONSUMER BAHAVIOR OF HOUSEWIFES IN DONOREJO VILLAGE, DEMAK ? - Siti Barokah; Ira Setiawati; Rita Meiriyanti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study was to determine the effect of lifestyle, financial literacy, and self-control on the consumptive behavior of housewifes in Donorejo Village Demak. This study uses a quantitative descriptive which describes the condition of the facts with the data collected from a questionnaire based on direct observation of the housewife in Donorejo Demak village. The population in this study were all housewifes from Donorejo Demak village, totaling 208 housewifes and the analysis technique used was multiple linear regression analysis, using SPSS, and it was found that lifestyle and financial literacy had an effect on consumptive behavior and self-control had no effect on consumer behavior. Keywords: lifestyle, financial literacy, self-control, consumer behavior.